Perceived Barriers to Youth Entrepreneurship in Pakistan and Hungary - Kazmi, Syed Zaheer Abbas (International Journal of Engineering and Management Sciences, 2018)
Entrepreneurship brings enormous benefits. It generates employment and helps in social and economic development. Ventures created through the youth entrepreneurship have enormous benefits. They generate employment, reduce poverty and unequitable distribution of wealth. These ventures do also help in social, economic and technological development. However, the youth faces several barriers to entrepreneurship. This study explores the personal & psychological, family related, institutional & regulatory, cultural & social, financial and market & knowledge barriers faced by the youth of Hungary and Pakistan. Qualitative research methodology was applied. Interviews at micro and meso levels were conducted from the young entrepreneurs and university professors of Pakistan and Hungary. Results indicate that Pakistan and Hungary have almost similar levels of Personal & Psychological barriers, however, the fear of failure is higher in Hungary than in Pakistan. Family related, cultural & social and market & knowledge barriers are higher in Pakistan for the youth entrepreneurship than Hungary. Institutional & regulatory and financial barriers are at medium levels in Pakistan. For Hungary, these are at low levels. The study has important implications for researchers, academicians, policy makers and for the young aspiring entrepreneurs.